The Influence Of Product Quality, Price, And Brand Image On Purchasing Decisions For Honda Motorbikes With Purchase Intention As An Intervening Variable - Murniasih, Siti; Prabowo, Heri; Sijabat, Rauly (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this research is motivated by the increasing need for people to use motorcycle vehicles. Motorcycles are now a popular choice because they facilitate daily activities outside the home. The ease and speed of reaching your destination makes riding a motorcycle an economical choice for those who want to travel. The purpose of this study was to determine the effect of product quality, price and brand image on purchasing decisions for Honda motorbikes with purchase intention as an intervening variable. This study uses a quantitative method with a sample size of 140 respondents. The sampling technique used was purposive sampling using the SmartPls tool as a testing tool. The results of this study indicate that the variables of product quality and brand image have an effect on buying interest. Price, brand image and purchase intention variables affect purchasing decisions. The brand image variable has an effect on purchasing decisions mediated by buying interest. while the price variable has no effect on buying interest. The product quality variable has no effect on buying interest. And product quality and price variables have no effect on purchasing decisions mediated by buying interest.